Autonet: A High-Speed, Self-Configuring Local Area Network Using Point-to-Point Links - Rodeheffer, Thomas L.; Thacker, Chuck; Birrell, Andrew; Rodeheffer, Tom; Murray, Hal; Schroeder, Michael; Satterthwaite, Ed; Needham, Roger; Burrows, Mike; Schroeder, M. D.; Schroeder, Mike (IEEE Journal on Select Areas of Communication, 1991)
Autonet is a self-configuring local area network composed of switches interconnected by 100 Mbit/second, full-duplex, point-to-point links. The switches contain 12 ports that are internally connected by a full crossbar. Switches use cut-through to achieve a packet forwarding latency as low as 2 microseconds per switch. Any switch port can be cabled to any other switch port or to a host network controller. A processor in each switch monitors the network’s physical configuration. A distributed algorithm running on the switch processors computes the routes packets are to follow and fills in the packet forwarding table in each switch. This algorithm automatically recalculates the forwarding tables to incorporate repaired or new links and switches, and to bypass links and switches that have failed or been removed. Host network controllers have alternate ports to the network and fail over if the active port stops working. With Autonet, distinct paths through the set of network links can carry packets in parallel. Thus, in a suitable physical configuration, many pairs of hosts can communicate simultaneously at full link bandwidth. The aggregate bandwidth of an Autonet can be increased by adding more links and switches. Each switch can handle up to 2 million packets/second. Coaxial links can span 100 meters and fiber links can span two kilometers. A 30-switch network with more than 100 hosts is the service network for Digital’s Systems Research Center .